Pengaruh Berbagai Media Tanam terhadap Pertumbuhan Microgreen Bunga Matahari (Helianthus annuus) - Arimah, Sinta; Kaswinarni, Fibria; Rachmawati, Rivanna Citraning (Biocaster : Jurnal Kajian Biologi, 2025)
Microgreens are young plants harvested when they are 7–14 days old after planting (DAP) with a nutrient content 40 times higher than mature plants, especially vitamins and phytonutrients. This study aims to determine the effectiveness of various growing media on the growth of sunflower microgreens. The study used a Randomized Block Design (RBD) with one factor of growing media (M1: sandy soil, M2: charcoal husk, M3: cocopeat, M4: rockwool) and three replicates, then the sampling process on each thinwall was 10 plants. The observation data were analyzed using a one-way Analysis of Variance (ANOVA) test to determine the differences between treatments. If the ANOVA results showed significance (< 0.05), then a further Honest Significant Difference (HSD) test was conducted at a significance level of 5% to identify treatments that were significantly different. Comparisons between treatments were presented in bar graphs. The results showed that cocopeat growing media provided the best growth response with an average plant height of 13.53 cm and wet weight of 32.8 g, which was significantly superior to other media. The superiority of cocopeat is supported by its physical and chemical properties, which are able to retain moisture, provide nutrients, and support root development. Thus, cocopeat is recommended as an effective growing medium for sunflower microgreen production.